Stres Finansial sebagai Faktor Risiko Quarter-Life Crisis pada Mahasiswa Tingkat Akhir - Mario Cristianto; Adelina Rahmawati (Universitas Muhammadiyah Metro, 2026)
The transition from university to the professional world often triggers profound anxiety among final-year students, a phenomenon commonly known as the quarter-life crisis (QLC). This condition is frequently exacerbated by individual economic uncertainty. This study aims to analyze the influence of financial stress on the quarter-life crisis among final-year students at Universitas Negeri Semarang. Beyond academic pressures, contemporary final-year students grapple with economic realities that subtly erode their psychological stability as they prepare for societal integration. The study employed a quantitative approach with a causal-associative design. It involved 394 respondents aged 18 to 25 years (enrolled in semesters 7 to 13), selected through simple random sampling. The research instruments consisted of a highly reliable adapted financial stress scale (Î± = 0.97) and a quarter-life crisis scale (Î± = 0.926), both utilizing a 4-point Likert scale. Data were collected online and analyzed using simple linear regression. The results revealed a significant positive influence of financial stress on the quarter-life crisis (r = 0.703; p < 0.05). These findings indicate that financial stress significantly contributes to the heightened intensity of existential crises; the higher the perceived economic pressure, the greater the students' vulnerability to future uncertainty and identity crises. A distinguishing feature of this study is the finding that financial stress acts as a primary catalyst for